Operation of water resource recovery facilities (Manual of practice ;, 2017)
"The water industry's cornerstone text -- reflecting the latest trends, technologies, and regulations. Operation of Water Resource Recovery Facilities (MOP 11), Seventh Edition, delivers state-of-the-art guidance on best practices in the operation, management, and maintenance of water resource recovery facilities. Now conveniently presented in one volume, this authoritative reference reflects the role of 21st-century facilities in recovering valuable resources, including water, nutrients, and energy, and also features updated information on activated sludge, anaerobic digestion, biological nutrient removal, chemical handling, dissolved air flotation, fixed-film processes, maintenance, odor management, and safety and security. Changes can be found throughout to keep pace with technological advances, including instrumentation and control systems, and reporting requirements."